Assessing the degree of maerl habitat fragmentation affecting fish species richness and abundance - Valliant, Michelle, 1991- (2020)
Verkefnið er lokað til 1.6.2022. Maerl beds are a type of habitat that consists of calcified red algae (Corallinales sp.). It is claimed by past studies that maerl beds are essential for juvenile gadoid fish nursery grounds (like the Atlantic cod (Gadus morhua), a critical exploited demersal fish species). A study performed underwater SCUBA diving surveys to estimate the abundance of fish and species richness of inner and exterior fragmented regions of maerl patches. Furthermore, the Starfish 452F side-scan sonar system was used to map the maerl habitat while the Gemini 720im SeaTec System was later tested to distinguish fish abundance, size, and species distribution. The study was conducted in Ísafjörður of Ísafjarðardjúp, where two maerl beds were surveyed and compared to an area of little to no maerl coverage (<20%). The interior of both maerl patches had a higher amount of fish species richness and abundance compared to the exterior areas of the patches, supporting edge effects. Also, the Gemini 720im SeaTec was tested where images of living unidentifiable organisms were able to be captured. It is encouraged to continue future testing of the system to assess fish populations within fragmented maerl patches. In conclusion, this study aimed to support the role that maerl plays for the early life stages of gadoid fish species. This study creates standardized procedures on marine habitat mapping, underwater SCUBA diving surveys, and multibeam imaging sonar systems. Overall, this research highlights the importance of continuous maerl habitats for marine conservation, which supports their importance of nursery grounds to recruit fish stocks. Kalkþörungabreiður eru tegund búsvæða sem saman standa af kölkuðum rauðþörungum (Corallinales sp.). Fyrri rannsóknir sýna að kalkþörungasvæði eru mikilvæg búsvæði fyrir ungviði fiskitegunda eins og Atlantshafsþorsk (Gadus morhua) og aðrar tegundir botnfisks. Í þessari rannsókn voru gerðar talningar á fiskum og öðrum stærri tegundum með SCUBA köfun til að bera saman ...